2021
DOI: 10.1186/s43088-020-00091-7
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis, characterization, and antibacterial activity of ZnO nanoaggregates using aqueous extract from Anacardium occidentale leaf: comparative study of different precursors

Abstract: Background Various parts of Anacardium occidentale plant possess curative qualities like antidiabetic, anti-inflammatory, antibacterial, antifungal, and antioxidant. Aqueous extract of this plant leaf was used in biosynthesizing zinc oxide (ZnO) nanoaggregates using two precursors of zinc salt (zinc acetate dihydrate [Zn(CH3COO)2∙2H2O] and zinc chloride [ZnCl2]). The synthesized ZnO samples were used in a comparative study to investigate the antibacterial activity against selected Gram-positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Zinc oxide (ZnO) nanoparticles (NPs) were created utilizing thyme leaf extract using a green technique, according to ST Karam et al The formation of the nanoparticles were spherical in shape with an average size in the range of 39.4–51.86 nm [ 51 ]. In a study conducted by Droepenu et al, Anacardium occidentale leaf extract was used to produce ZnO NPs with two precursors of zinc salt (zinc acetate dihydrate and zinc chloride) and evaluated against Acinetobacter baumannii , Escherichia coli , Staphylococcus aureus , and Exiguobacterium aquaticum [ 52 ]. Zinc nitrate hexahydrate was used as a precursor to producing ZnO nanoparticles from the Vitex negundo plant, which demonstrated bacterial inhibition against pathogenic gram-positive and gram negative bacteria [ 53 ].…”
Section: Green Synthesis Of Nanomaterialsmentioning
confidence: 99%
“…Zinc oxide (ZnO) nanoparticles (NPs) were created utilizing thyme leaf extract using a green technique, according to ST Karam et al The formation of the nanoparticles were spherical in shape with an average size in the range of 39.4–51.86 nm [ 51 ]. In a study conducted by Droepenu et al, Anacardium occidentale leaf extract was used to produce ZnO NPs with two precursors of zinc salt (zinc acetate dihydrate and zinc chloride) and evaluated against Acinetobacter baumannii , Escherichia coli , Staphylococcus aureus , and Exiguobacterium aquaticum [ 52 ]. Zinc nitrate hexahydrate was used as a precursor to producing ZnO nanoparticles from the Vitex negundo plant, which demonstrated bacterial inhibition against pathogenic gram-positive and gram negative bacteria [ 53 ].…”
Section: Green Synthesis Of Nanomaterialsmentioning
confidence: 99%
“…The use of zinc chloride has led to the synthesis of ZnO nanorods that were 167 nm in length and 68 nm in width. However, both samples faced aggregation [ 148 ]. The ZnO NPs synthesized from zinc sulphate had a nanorod morphology and an average size of 30 nm when Justicia adhatoda leaf extract was used.…”
Section: Factors Affecting the Biological Synthesis Of Nanoparticlesmentioning
confidence: 99%
“…Sambucus ebulus-mediated ZnO nanoparticles explain efficient antioxidant and antibacterial activity [86]. Droepenu, Eric Kwabena, et al reported the biosynthesis of ZnO nanoparticles using Anacardium occidentale and tested against S. aureus (ZOI = 1.06 ± 0.14 mm), E. aquaticum (ZOI = 1.99 ± 0.11 mm), K. pneumoniae (ZOI = 2.08 ± 0.03 mm), E. coli (ZOI = 1.49 ± 0.09 mm), and A. baumanii (ZOI = 2.99 ± 0.01 mm) [87].…”
Section: Synthesis Of Zno Nanoparticles Using Leaf: (2019-2021)mentioning
confidence: 99%